Early symptomatic benefit indicates long-term prognosis after transcatheter mitral valve edge-to-edge repair in functional and degenerative etiology. (1st December 2021) - Geyer, Martin; Keller, Karsten; Tamm, Alexander R.; Born, Sonja; Bachmann, Kevin; Ruf, Tobias Friedrich; Kreidel, Felix; Hahad, Omar; Petrescu, Aniela; Schnitzler, Katharina; Schmitt, Volker H.; da Rocha e Silva, Jaqueline Grace; et al.
Abstract: Background: Mitral regurgitation (MR) is common in patients with heart failure and constitutes an independent risk factor for adverse prognosis besides NYHA-class. The predictive value of dyspnea reduction after transcatheter mitral valve repair (TMVr) on outcome has not been investigated up to now. Methods and results: We enrolled 627 consecutive patients (47.0% female, 57.4% functional MR; median follow-up 486 days[IQR 157/961]; survival status available in 96.8%; symptoms assessed in n = 556 at baseline / n = 406 at 1 month) treated with isolated percutaneous mitral valve edge-to-edge repair in our center from 06/2010–03/2018 (exclusion of combined forms of TMVr) in a monocentric retrospective analysis. Survival was 97.6% at discharge, 73.9% after 1, 54.5% after 3, 37.6% after 5 and 21.7% after 7-years. Before TMVr, NYHA-classes III/IV were found in 89.0%. Of these, 74.7% reported symptomatic relief (reduction in NYHA-class) one month after procedure (NYHA class recorded in 406 patients at 30 days). NYHA-classes III/IV were documented in 37.2% ( p < 0.001) at 30 days and in 36.6% (p < 0.001) at 1 year without significant changes between the follow-ups. Dyspnea reduction was accompanied by significantly improved long-term survival (1 year, 89.1 vs 71.2%, p = 0.001, 2 years: 75.5 vs 58.7%, p = 0.039) and was identified as an independent predictor for lower mortality (1-year HR for increased mortality by missing symptomatic improvement 2.94 [95%CI 1.53–5.65], p = 0.001; long-term HR 1.95 [95%CI 1.29–2.94], p = 0.001) independently in both etiologies of MR. Conclusion: TMVr by edge-to-edge therapy enables early and sustainable symptomatic improvement in nearly 75% of the symptomatic patients. The simple assessment of postinterventional changes in NYHA-class might serve as an independent predictor for mid- and long-term prognosis in both FMR and DMR. Graphical abstract: Unlabelled Image Highlights: Mitral regurgitation is an well-established risk factor for adverse prognosis in HF. interventional therapy enables sustainable symptomatic improvement in nearly 75%. Postprocedural change in NYHA-class might be a tool predict prognosis after TMVr.